UPAYA MENURUNKAN PENGGUNAAN ANTIBIOTIKA PADA PENGOBATAN ISPA MELALUI SELF-MONITORING DI PUSKESMAS KOTA SINGKAWANG - , Yearmi Wirinar, S.Si, Dra. Siti Munawaroh, Apt., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background. Acute respiratory infection (ARI) disease is the most enormous number at Singkawang City. In 2005, the prevalence of non pnemonia ARI was 50.5%. The antibiotics utilization for ARI in 2006 reached 89.8%. Some efforts have been conducted to improve rational drug utilization at the public health centers but it is still far from intended goal. Hence, through this study, it is conducted a self-monitoring intervention as an effort to decrease antibiotics utilization toward ARI treatment at the public health centers. Objective. This study was conducted to evident whether self-monitoring intervention can decrease antibiotics utilization and polypharmaceutical for ARI treatment, by using parameters of patient those treated with antibiotics and a mean of drugs per presciption (polypharmaceutical). Method. This is an quasy-experimental study by non-randomized pretestpostes control group design. The analysis unit is some public health centers. The study divided into two groups, of equal treatment and control groups as 8 public health centers. The subjects were physicians and professionals at the public health centers. The prescription data was collected for 3 months before and after interventions. The collected data was then analyzed by calculating percentage of antibiotics utilization and polypharmaceutical monthly. It was then tabulated and analyzed by statistical Kruskal-Willis Test and Mann-Whitney Test. Results. After self-monitoring intervention conducted, the treatment group yielded a decreased numbers of antibiotics utilization from 69.2% (before) to 31.7% (after) intervention (reduced 54.2%), and the polypharmaceutical was decreased from 4.8 (before) to 4.3 (after) intervention (reduced 10.4%). For the control group, there was no decreased number occured, in contrary, it found an increased number of antibiotics utilization from 64.7% (before) to 67.7% (after) intervention given (increased to 4.4%), and also similarly, the polypharmaceutical was also increased from 4.8 (before) to 5 (after) interventian given (increased to 4%) Conclusion. It was concluded that self-monitoring intervention conducted by public health and followed up by a feedback given by the District Health Team may decrease antibiotics utilization and polypharmaceutical toward ARI treatment.